Réponses

  • Utilisateur Brainly
2014-03-11T13:41:22+01:00
Bonjour,

49x²-(5x-3)²

dev et reduire : 49x²-(25x²-30x+9) = 49x²-25x²+30x-9 = 24x²+30x-9

facto : [7x-(5x-3)][7x+(5x-3)] = (7x-5x+3)(7x+5x-3) = (2x+3)(12x-3) = 3(2x+3)(4x-1)

pour x = 1/4
je prends la forme dev : 24(1/4)² +(30*1/4) -9
                                       24/16 + 30/4 -9 =
                                       3/2 + 15/2 -18/2 = 0

2) (3x-1)²-(2x-1)(6x-2) =
9x²-6x+1)-(12x²-4x-6x+2) =
9x²-6x+1-12x²+10x-2 =
-3x²+4x-1

facto (6x-2) = 2(3x-1)

(3x-1)²-2(3x-1)(2x-1) =
(3x-1)[(3x-1)-2(2x-1)] =
(3x-1)(3x-1-4x+2) =
(3x-1)(-x+1)



2014-03-11T13:44:27+01:00
Bonjour,

49x²-(5x-3)²

dev et reduire : 49x²-(25x²-30x+9) = 49x²-25x²+30x-9 = 24x²+30x-9

facto : [7x-(5x-3)][7x+(5x-3)] = (7x-5x+3)(7x+5x-3) = (2x+3)(12x-3) = 3(2x+3)(4x-1)

pour x = 1/4
je prends la forme dev : 24(1/4)² +(30*1/4) -9
                                       24/16 + 30/4 -9 =
                                       3/2 + 15/2 -18/2 = 0

2) (3x-1)²-(2x-1)(6x-2) =
9x²-6x+1)-(12x²-4x-6x+2) =
9x²-6x+1-12x²+10x-2 =
-3x²+4x-1

factoriser (6x-2) = 2(3x-1)

(3x-1)²-2(3x-1)(2x-1) =
(3x-1)[(3x-1)-2(2x-1)] =
(3x-1)(3x-1-4x+2) =
(3x-1)(-x+1)


 a plus